Pelatihan Digital Mindset untuk Meningkatkan Kompetensi Guru dalam Penguatan Pembelajaran Inovatif dan Berkelanjutan - Muhammad Japar; Nadiroh Nadiroh; Hermanto Hermanto; Eti Dwi Wiraningsih; Karisdha Pradityana; Nurul Kusniah (Politeknik Piksi Ganesha Indonesia, 2026)
Digital mindset training for teachers is essential in addressing the challenges of learning in the digital era, particularly in improving innovative and sustainable pedagogical competencies. The problems faced include limited understanding of digital mindset concepts, the tendency to use technology at a technical level, and the lack of pedagogically oriented training. This activity aimed to enhance the competencies of junior high school PPKn teachers in DKI Jakarta through digital mindset training. The methods included needs identification, training design and implementation through seminars, interactive discussions, and practical sessions, as well as evaluation using pre-test and post-test. The activity involved 35 participants from the MGMP PPKn SMP. The results showed an increase in understanding, indicated by the rise in average scores from 62.4 to 82.7 and supported by significant t-test results. In addition, teachers’ perspectives shifted toward a more collaborative and pedagogical use of technology. This training effectively improved teachers’ competencies in developing innovative and sustainable learning.